Graphite and graphene-containing polyimide mixed glue and preparation process thereof

By modifying graphene with aminosilane and bifunctional coupling agent, the graphene/graphene dispersion and interfacial compatibility problems in polyimides are solved, and the thermal conductivity, mechanical strength and fatigue resistance of the composite material are improved. , ensuring high temperature stability and durability for long-term use.

CN119264868APending Publication Date: 2025-01-07李恒飞
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411679553.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

There are dispersion and interface compatibility problems in the composite process of polyimide and graphite/graphene, which leads to a decrease in uniformity of the composite material, affecting its mechanical properties and bonding effect.

Method used

Modify the graphite surface by aminosilane, enhance its hydrogen bond interaction with the polyimide precursor, inhibit graphite agglomeration, and modify graphene through a bifunctional coupling agent to enhance its in polyimide matrix The dispersion and interface binding force form a stable and continuous thermal conductivity path and a tight interface binding network.

Benefits of technology

It significantly improves the thermal conductivity, mechanical strength, tensile and compressive properties of composite materials, enhances fatigue resistance and high-temperature chemical stability, ensures the mechanical and thermal conductivity of the material in high-temperature environments, and extends the material's Service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264868A_ABST
    Figure CN119264868A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesive synthesis, and particularly relates to polyimide mixed glue containing graphite and graphene and a preparation process of the polyimide mixed glue. The mixed glue comprises the following components in parts by weight: 4-6 parts of modified graphite, 1-2 parts of modified graphene, 45-50 parts of N, N-dimethylformamide, 10-12 parts of a rigid diamine monomer, 8-10 parts of a flexible diamine monomer, 6-8 parts of a diamine monomer with a main chain containing an ester group and 18-20 parts of an aromatic anhydride monomer. According to the present invention, the aminosilane modified graphite and the bifunctional coupling agent modified graphene are adopted to enhance the dispersibility and the chemical binding force in the polyimide matrix so as to form the stable heat conduction path, and improve the thermal conductivity and the mechanical strength of the material, and the modified graphite and the modified graphene are uniformly dispersed in the aprotic polar solvent so as to avoid the agglomeration; and the stable performance under high temperature and long-term use is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive synthesis, and in particular relates to a polyimide mixed glue containing graphite and graphene and a preparation process thereof. Background Art

[0002] As a type of high-performance polymer material, polyamide is highly respected in many fields for its excellent high temperature resistance, chemical stability and mechanical strength, and is widely used in high-demand scenarios such as structural materials, electronic packaging, and heat-resistant coatings. The amide bonds in the polyimide molecular chain can form strong hydrogen bonds between molecules, so that the material has excellent stability even under high temperature, high pressure and strong corrosion environments. At the same time, the excellent mechanical properties and chemical stability of polyimide make it show durability and reliability superior to ordinary polymers in many engineering fields. In terms of further improving the performance of polyimide, the addition of graphite and graphene provides great development potential. Graphite is a layered carbon material, which is widely used in thermal management and material systems with high conductivity requirements due to its excellent electrical and thermal conductivity. Graphene is a two-dimensional material composed of a single layer of carbon atoms, with an extremely high specific surface area and superior mechanical strength. Its unique molecular structure brings extraordinary electrical conductivity, thermal conductivity and tensile strength. Therefore, adding graphite or graphene to the polyimide matrix can not only greatly improve the electrical conductivity and thermal conductivity of the composite material, but also improve its overall mechanical strength and durability. As a result, the polyimide-graphite / graphene composite glue has unique advantages, showing excellent properties such as high strength, heat resistance and thermal conductivity, which makes it show broad application prospects in high-performance application fields such as electronic component packaging, composite structure bonding and thermal conductive adhesives. This composite material can not only meet the bonding requirements of high-demand structures, but also significantly improve the thermal management efficiency of the equipment, help to extend the life of the device, and enhance its reliability and durability. However, the dispersibility and interfacial compatibility problems in the composite process of polyimide and graphite / graphene are the main obstacles to the further development of such composite materials. Due to the hydrophobicity of graphite and graphene, they are difficult to disperse evenly in the hydrophilic matrix of polyimide and are prone to agglomeration, which leads to a decrease in the uniformity of the composite material and affects its mechanical properties and bonding effect. Therefore, based on the above challenges, it is extremely necessary to develop a polyimide-based mixed glue with good dispersibility, high interfacial compatibility and excellent bonding performance. Summary of the invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide a polyimide mixed glue containing graphite and graphene and a preparation process thereof.

[0004] The technical effect described in the present invention is achieved through the following technical scheme: a polyimide mixed glue containing graphite and graphene, which comprises the following components by weight: 4 to 6 parts of modified graphite, 1 to 2 parts of modified graphene, 45 to 50 parts of N, N-dimethylformamide, 10 to 12 parts of rigid diamine monomers, 8 to 10 parts of flexible diamine monomers, 6 to 8 parts of diamine monomers containing ester groups in the main chain and 18 to 20 parts of aromatic anhydride monomers.

[0005] Preferably, the specific preparation steps of the modified graphite are as follows: A1: After washing the graphite with deionized water, dry it at 100-120°C to constant weight to obtain dry graphite; add 3-aminopropyltriethoxysilane to anhydrous ethanol, stir and dissolve evenly to obtain a coupling agent solution with a concentration of 1-3wt%; A2: adding the dried graphite prepared in step A1 to the coupling agent solution prepared in step A1, ultrasonically treating at 100-200W for 15-30min, heating to 70-80°C, stirring at 200rpm for 4-6h, centrifuging at 5000rpm for 10min, filtering, and vacuum drying at 80-100°C to constant weight to obtain modified graphite; Preferably, in step A2, the ratio of the amount of the dry graphite to the amount of the coupling agent solution is 1 g: 30-50 mL.

[0006] Preferably, the specific preparation steps of the modified graphene are as follows: B1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature to 0-5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add potassium permanganate, raise the temperature to 35-40°C after the addition is complete, stir and react for 12-24 hours, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution for 3 times, dry at 60°C to constant weight, and obtain graphene oxide; B2: Disperse the graphene oxide prepared in step B1 in dimethyl sulfoxide, and perform ultrasonic treatment at 200W for 30 to 60 minutes to obtain a graphene oxide dispersion; slowly drop 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 0 to 5°C and continue stirring, after the dropwise addition is completed, heat to 60°C, continue stirring for 12 to 24 hours, and cool to room temperature after the reaction is completed to obtain an amination graphene solution; B3: Add succinic anhydride to the amination graphene solution prepared in step B2, stir at 300 rpm and heat to 60-80°C, react for 2-4 hours, cool to room temperature, wash repeatedly with deionized water and ethanol 5 times, centrifuge at 8000 rpm for 10 minutes, and dry at 60°C to constant weight to obtain modified graphene; Preferably, in step B1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-5mL:1g; Preferably, in step B2, the ratio of the amount of graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 2 mg: 1-2 mL: 0.02-0.03 mL; Preferably, in step B3, the mass ratio of the succinic anhydride to the graphene oxide in step B2 is 1:5.

[0007] Preferably, the rigid diamine monomer is any one of p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)diaminobiphenyl, and 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl.

[0008] Preferably, the flexible diamine monomer is any one of 4,4'-diaminodiphenyl ether, bis(4-aminophenyl)terephthalate, 1,3'-bis(4'-aminophenoxy)benzene and 2,2'-bis[4-(4-aminophenoxyphenyl)propane].

[0009] Preferably, the ester group-containing diamine monomer is any one of [4-(4-aminobenzoyl)oxyphenyl]4-aminobenzoate and bis(4-aminophenyl)terephthalate.

[0010] Preferably, the aromatic anhydride monomer is selected from any one of p-phenylene-diphthalic anhydride, 4,4-oxydiphthalic anhydride, 4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, 4,4'-biphenyltetracarboxylic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic anhydride.

[0011] Preferably, another aspect of the present invention is to provide a method for preparing a polyimide mixed glue containing graphite and graphene, and the specific preparation steps are as follows: S1: After the modified graphite and modified graphene are ground and screened through an 80-mesh sieve, they are added to N,N-dimethylacetamide, subjected to 60W ultrasonic treatment for 30 minutes, and stirred at 300 rpm for 30 to 60 minutes. After uniform dispersion, rigid diamine monomer and flexible diamine monomer are added in sequence at room temperature, stirred and dissolved uniformly, and allowed to stand for 15 minutes to obtain a precursor mother solution; S2: Under nitrogen protection, the temperature is raised to 30°C, the aromatic anhydride monomer is dried and added to the precursor mother solution prepared in step S1 in 3 to 5 batches, and after the aromatic anhydride is added, the temperature is gradually raised to 50°C at a rate of 1°C / min, and stirring is continued for 4 hours. After the reaction is completed, it is allowed to stand and cool to room temperature to obtain a mixed solution; S3: Adding the diamine monomer containing an ester group in the main chain to the mixed solution prepared in step S2 in three batches, stirring continuously at 300 rpm for 20 to 30 min, standing at room temperature for 1 h, then raising the temperature to 80° C., stirring continuously for 100 to 120 min, evaporating under reduced pressure to remove the solvent, and cooling to room temperature to obtain a polyimide mixed glue.

[0012] Preferably, the specific parameters of the reduced pressure evaporation in step S3 are temperature 40-50° C., pressure 150-300 mbar, rotation speed 100-200 rpm, and time 1-3 h.

[0013] The beneficial effects of the present invention are as follows: The present invention modifies the graphite surface by aminosilane so that it carries an amino group, can form weak interactions such as hydrogen bonds with diamine monomers and aromatic anhydrides in polyimide precursors, and enhance the dispersibility of graphite in polyimide matrix; under the action of aprotic polar solvents, the agglomeration of graphite is effectively suppressed, and the affinity brought by aminosilane modification ensures the uniform distribution of graphite in the matrix, forming a stable and continuous heat conduction path. This uniform distribution not only improves the thermal conductivity of the material, but also increases the mechanical strength of the overall structure, and enhances the tensile and compressive properties of the material. Graphene is surface-modified by a bifunctional coupling agent (amino-carboxyl), and the amino and carboxyl groups in the coupling agent form multiple chemical bonds with the diamine and aromatic anhydrides of the polyimide precursor, respectively, significantly enhancing the chemical binding force of graphene in the matrix, so that graphene obtains excellent dispersibility and stability in the polyimide matrix, forming a tight interface binding network, and significantly improving the overall performance of the composite material. The multiple bonding structures formed by the bifunctional coupling agent on the graphene surface can act as a "stress buffer" especially when the material is under stress, effectively preventing local fracture, improving the material's impact resistance and ductility, and significantly enhancing the fatigue resistance of the composite material.

[0014] The present invention utilizes aminosilane-modified graphite as a stable reinforcing phase, and its uniform distribution in the matrix and strong interface bonding force provide an efficient and coherent heat conduction path for the composite material, significantly improving thermal conductivity. The bifunctional coupling agent modification of graphene further enhances the interface compatibility, avoids thermal resistance caused by interface defects, ensures efficient conduction of heat in the matrix, and enhances the overall thermal management capability of the material. To ensure stability under high temperature conditions, the present invention utilizes nitrogen protection and a method of adding aromatic anhydrides step by step during the synthesis process, giving the polyimide precursor excellent high temperature resistance and chemical resistance, and the interface bonding force of the graphite and graphene modified by the coupling agent and the polyimide precursor is further improved, avoiding the problem of delamination and interface peeling under high temperature environment, and this strong interface bonding enables the composite material to still maintain excellent mechanical properties and thermal conductivity under high temperature environment. In addition, the multiple bonding effects formed by the bifunctional coupling agent on the graphene surface significantly reduce the risk of chemical degradation at the interface and extend the service life of the material. Aminosilane-modified graphite has an antioxidant effect, which improves aging resistance and ensures that the material can maintain good strength and stability under long-term environmental changes, making it suitable for applications that require long-term use.

[0015] The present invention improves the initial dispersion effect of graphite and graphene by using a non-protonic polar solvent (N,N-dimethylformamide), and at the same time, the modification of aminosilane and bifunctional coupling agent ensures the stability of viscosity of composite precursor in the preparation process, facilitates the operability of glue in application, and is suitable for various application modes with high dispersibility and stable viscosity, thereby ensuring the high performance effect of adhesive; the non-protonic polar solvent ensures the uniform dispersion of graphite and graphene, and the synergistic effect of flexible and rigid diamine monomers enables the material to form a complete heat conduction path during molding; the modification of aminosilane and bifunctional coupling agent effectively avoids interface defects in heat conduction and improves thermal conductivity.

[0016] In summary, the bifunctional structure used in the present invention has a good interface combination with the polyimide precursor, so that the material has excellent stability in high temperature, high humidity and corrosive environments, and is particularly suitable for bonding and thermal conductivity applications in high temperature and harsh environments for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a heating analysis test diagram of the polyimide mixed glue prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4; Figure 2 It is a viscosity stability test chart of the polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a test graph of the peel strength of the polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 4 It is a tensile strength test graph of the polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0020] Embodiment 1: A polyimide mixed glue containing graphite and graphene, comprising the following components in parts by weight: 4 parts of modified graphite, 1 part of modified graphene, 45 parts of N,N-dimethylformamide, 10 parts of rigid diamine monomers, 8 parts of flexible diamine monomers, 6 parts of diamine monomers containing ester groups in the main chain and 18 parts of aromatic anhydride monomers.

[0021] The specific preparation steps of modified graphite are as follows: A1: After washing the graphite with deionized water, dry it at 100°C to constant weight to obtain dry graphite; add 3-aminopropyltriethoxysilane to anhydrous ethanol, stir and dissolve evenly to obtain a coupling agent solution with a concentration of 3wt%; A2: Add 10 g of dry graphite prepared in step A1 to 300 mL of coupling agent solution prepared in step A1, treat with 100 W ultrasonic wave for 30 min, heat to 70 ° C, stir at 200 rpm for 6 h, centrifuge at 5000 rpm for 10 min, filter, and vacuum dry at 80 ° C to constant weight to obtain modified graphite; The specific preparation steps of modified graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 300mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 35°C, stir and react for 24h, after the reaction is complete, slowly add 800mL of deionized water to dilute, then add 30mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60°C to constant weight, and obtain graphene oxide; B2: Disperse 1 g of graphene oxide prepared in step B1 in 500 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 30 min to obtain a graphene oxide dispersion; slowly drop 10 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 5°C and continue stirring, after the dropwise addition is completed, heat to 60°C, continue stirring for 12 h, and cool to room temperature after the reaction is completed to obtain an amination graphene solution; B3: Add 200 mg of succinic anhydride to the amination graphene solution prepared in step B2, stir at 300 rpm and heat to 60°C, react for 4 hours, cool to room temperature, wash with deionized water and ethanol repeatedly for 5 times, centrifuge at 8000 rpm for 10 minutes, and dry at 60°C to constant weight to obtain modified graphene; The specific preparation steps of polyimide mixed glue are as follows: S1: After the modified graphite and modified graphene are ground and screened through an 80-mesh sieve, they are added to N,N-dimethylacetamide, subjected to 60W ultrasonic treatment for 30 minutes, and stirred at 300 rpm for 30 minutes. After uniform dispersion, p-phenylenediamine and 4,4'-diaminodiphenyl ether are added in sequence at room temperature, stirred and dissolved uniformly, and allowed to stand for 15 minutes to obtain a precursor mother solution; S2: Under nitrogen protection, the temperature was raised to 30°C, the aromatic anhydride monomer was dried and added to the precursor mother solution prepared in step S1 in 3 batches, and after adding p-phenylene-diphenyltrimethylol dianhydride, the temperature was gradually raised to 50°C at a rate of 1°C / min, and stirring was continued for 4 hours. After the reaction was completed, the mixture was allowed to stand and cool to room temperature to obtain a mixed solution; S3: Add [4-(4-aminobenzoyl)oxyphenyl]4-aminobenzoate to the mixed solution prepared in step S2 in three batches, stir continuously at 300 rpm for 20 min, let stand at room temperature for 1 h, then raise the temperature to 80°C, stir continuously for 100 min, and evaporate under reduced pressure. The specific parameters are temperature 40°C, pressure 150 mbar, rotation speed 100 rpm, time 3 h, remove the solvent, cool to room temperature, and obtain a polyimide mixed glue.

[0022] Example 2: A polyimide mixed glue containing graphite and graphene, comprising the following components in parts by weight: 5 parts of modified graphite, 1 part of modified graphene, 50 parts of N,N-dimethylformamide, 12 parts of rigid diamine monomers, 10 parts of flexible diamine monomers, 6 parts of diamine monomers containing ester groups in the main chain and 18 parts of aromatic anhydride monomers.

[0023] The specific preparation steps of modified graphite are as follows: A1: After washing the graphite with deionized water, dry it at 110°C to constant weight to obtain dry graphite; add 3-aminopropyltriethoxysilane to anhydrous ethanol, stir and dissolve evenly to obtain a coupling agent solution with a concentration of 2wt%; A2: Add 10 g of dry graphite prepared in step A1 to 500 mL of coupling agent solution prepared in step A1, treat with 150 W ultrasonic wave for 25 min, heat to 75 ° C, stir at 200 rpm for 5 h, centrifuge at 5000 rpm for 10 min, filter, and vacuum dry at 90 ° C to constant weight to obtain modified graphite; The specific preparation steps of modified graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 250mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 4°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 38°C, stir and react for 20h, after the reaction is complete, slowly add 1000mL of deionized water to dilute, then add 50mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60°C to constant weight, and obtain graphene oxide; B2: Disperse 1 g of graphene oxide prepared in step B1 in 1000 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 50 min to obtain a graphene oxide dispersion; slowly drop 12 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 4°C and continue stirring, after the dropwise addition is completed, heat to 60°C, continue stirring for 20 h, and cool to room temperature after the reaction is completed to obtain an amination graphene solution; B3: Add 200 mg of succinic anhydride to the amination graphene solution prepared in step B2, stir at 300 rpm and heat to 70°C, react for 3 h, cool to room temperature, wash with deionized water and ethanol repeatedly for 5 times, centrifuge at 8000 rpm for 10 min, and dry at 60°C to constant weight to obtain modified graphene; The specific preparation steps of polyimide mixed glue are as follows: S1: After the modified graphite and modified graphene are ground and screened through an 80-mesh sieve, they are added to N,N-dimethylacetamide, subjected to 60W ultrasonic treatment for 30 minutes, and stirred at 300 rpm for 45 minutes. After uniform dispersion, m-phenylenediamine and bis(4-aminophenyl)terephthalate are added in sequence at room temperature, stirred and dissolved uniformly, and allowed to stand for 15 minutes to obtain a precursor mother solution; S2: Under nitrogen protection, the temperature was raised to 30° C., the aromatic anhydride monomer was dried and added to the precursor mother solution prepared in step S1 in 4 batches, and after adding 4,4-oxydiphthalic anhydride, the temperature was gradually raised to 50° C. at a rate of 1° C. / min, and stirring was continued for 4 hours. After the reaction was completed, the mixture was allowed to stand and cool to room temperature to obtain a mixed solution; S3: Add bis(4-aminophenyl)terephthalate to the mixed solution prepared in step S2 in three batches, stir continuously at 300 rpm for 20 to 30 min, let stand at room temperature for 1 h, then increase the temperature to 80°C, stir continuously for 110 min, and evaporate under reduced pressure. The specific parameters are temperature 45°C, pressure 250 mbar, rotation speed 150 rpm, time 2 h, remove the solvent, cool to room temperature, and obtain a polyimide mixed glue.

[0024] Example 3: A polyimide mixed glue containing graphite and graphene, which comprises the following components in parts by weight: 6 parts of modified graphite, 2 parts of modified graphene, 48 parts of N,N-dimethylformamide, 11 parts of rigid diamine monomers, 9 parts of flexible diamine monomers, 7 parts of diamine monomers containing ester groups in the main chain and 19 parts of aromatic anhydride monomers.

[0025] The specific preparation steps of modified graphite are as follows: A1: After washing the graphite with deionized water, dry it at 120°C to constant weight to obtain dry graphite; add 3-aminopropyltriethoxysilane to anhydrous ethanol, stir and dissolve evenly to obtain a coupling agent solution with a concentration of 1wt%; A2: Add 10 g of dry graphite prepared in step A1 to 400 mL of coupling agent solution prepared in step A1, treat with 200 W ultrasonic wave for 15 min, heat to 80 ° C, stir at 200 rpm for 4 h, centrifuge at 5000 rpm for 10 min, filter, and vacuum dry at 100 ° C to constant weight to obtain modified graphite; The specific preparation steps of modified graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 220mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 0℃, stir and mix to disperse evenly, control the temperature to 10℃, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 40℃, stir and react for 12h, after the reaction is complete, slowly add 900mL of deionized water to dilute, then add 40mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60℃ to constant weight, and obtain graphene oxide; B2: Disperse 1 g of graphene oxide prepared in step B1 in 800 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 60 min to obtain a graphene oxide dispersion; slowly drop 15 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 0°C and continue stirring, after the dropwise addition is completed, heat to 60°C, continue stirring for 24 h, and cool to room temperature after the reaction is completed to obtain an amination graphene solution; B3: Add 200 mg of succinic anhydride to the amination graphene solution prepared in step B2, stir at 300 rpm and heat to 80°C, react for 2 h, cool to room temperature, wash with deionized water and ethanol repeatedly for 5 times, centrifuge at 8000 rpm for 10 min, and dry at 60°C to constant weight to obtain modified graphene; The specific preparation steps of polyimide mixed glue are as follows: S1: After the modified graphite and modified graphene are ground and screened through an 80-mesh sieve, they are added to N,N-dimethylacetamide, subjected to 60W ultrasonic treatment for 30 min, and stirred at 300 rpm for 60 min. After uniform dispersion, 2,2'-bis(trifluoromethyl)diaminobiphenyl and 2,2'-bis[4-(4-aminophenoxyphenyl)propane] are added in sequence at room temperature, stirred and dissolved uniformly, and allowed to stand for 15 min to obtain a precursor mother solution; S2: Under nitrogen protection, the temperature was raised to 30°C, the aromatic anhydride monomer was dried and added to the precursor mother solution prepared in step S1 in 5 batches, 4,4'-biphenyltetracarboxylic dianhydride was added and the temperature was gradually raised to 50°C at a rate of 1°C / min, and stirring was continued for 4 hours. After the reaction was completed, the mixture was allowed to stand and cool to room temperature to obtain a mixed solution; S3: Add [4-(4-aminobenzoyl)oxyphenyl]4-aminobenzoate to the mixed solution prepared in step S2 in three batches, stir continuously at 300 rpm for 30 min, let stand at room temperature for 1 h, then raise the temperature to 80°C, stir continuously for 120 min, evaporate under reduced pressure, the specific parameters are temperature 50°C, pressure 300 mbar, speed 200 rpm, time 1 h, remove the solvent, cool to room temperature, and obtain a polyimide mixed glue.

[0026] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that modified graphite is not added in Comparative Example 1, but only modified graphene is added.

[0027] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that modified graphene is not added in Comparative Example 2, but only modified graphite is added.

[0028] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that in Comparative Example 3, graphite and graphene are used instead of modified graphite and modified graphene.

[0029] Comparative Example 4: The operation of Comparative Example 4 is substantially the same as that of Example 2, except that ethyl acetate is used in Comparative Example 4 instead of N,N-dimethylformamide.

[0030] Performance Test: Heating analysis test: The polyimide mixed glue prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 was placed in a thermogravimetric analyzer, and the temperature was gradually increased from room temperature to 600°C at a rate of 10°C / min under a nitrogen atmosphere. The mass loss rate was measured at 100°C, 200°C, 400°C and 600°C, respectively. The mass loss rate = (mass before heating - mass after heating) / mass before heating × 100%. The results are as follows: Figure 1 shown.

[0031] Depend on Figure 1The results show that the polyimide mixed glue prepared by the present invention has excellent heat resistance and maintains a relatively low mass loss at a relatively high temperature; from the results of Comparative Example 1 and Example 2, it can be seen that in Comparative Example 1, there is a lack of modified graphite, the thermal conductive network is imperfect, and the heat cannot be effectively conducted, which leads to a local temperature increase and accelerates thermal decomposition. In addition, due to the lack of the interface reinforcement effect of the modified graphite, the bonding force between the filler and the matrix is ​​reduced, and delamination and peeling are prone to occur, which leads to an increase in mass loss; from the results of Comparative Example 2 and Example 2, it can be seen that in Comparative Example 2, the toughening effect of the modified graphene on the material is missing, the impact resistance and ductility are reduced, and cracks are more likely to occur during thermal decomposition. At the same time, due to the lack of a tight interface network of the modified graphene, the overall material The thermal stability decreases and the mass loss increases. It can be seen from the results of Comparative Example 3 and Example 2 that the unmodified filler used in Comparative Example 3 is easy to agglomerate and cannot be evenly dispersed in the matrix, forming defective areas, resulting in stress concentration. At the same time, there is a lack of effective chemical bonding between the unmodified filler and the matrix, and the interface bonding force is weak, which makes it easy to debond and delaminate at high temperatures. The agglomeration of the filler and multiple interface defects lead to a significant increase in the mass loss rate. It can be seen from the results of Comparative Example 4 and Example 2 that the solubility of ethyl acetate in the polyimide precursor in Comparative Example 4 is extremely poor, and a stable precursor solution cannot be formed, which may lead to incomplete polymerization. In addition, ethyl acetate evaporates in large quantities at relatively low temperatures, and the mass loss increases significantly at high temperatures, and the thermal stability is extremely poor.

[0032] Viscosity stability test: The polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4 was placed in an environment with a temperature of 70°C and a relative humidity of 90% for 14 days. Samples were taken out on the 3rd, 7th and 14th days to measure the viscosity, and the viscosity change was calculated as (test viscosity-initial viscosity) / initial viscosity×100%. The results are shown in FIG. Figure 2 shown.

[0033] Depend on Figure 2As a result, the polyimide mixed glue prepared by the present invention exhibits excellent stability in the accelerated stability test; from the results of Comparative Example 1 and Example 2, it can be seen that in Comparative Example 1, there is only modified graphene, lacking the synergistic effect of the modified graphite that forms hydrogen bonds with the polyimide matrix, the interface bonding force is weakened, the network structure inside the material is not perfect, and the activity of the polymer chain segments is increased, resulting in a decrease in viscosity under high temperature and high humidity environments; from the results of Comparative Example 2 and Example 2, it can be seen that in Comparative Example 2, there is only modified graphite, lacking the tight interface network formed by the modified graphene, lacking the "stress buffer zone" effect of the bifunctional coupling agent modified graphene, the material's ability to resist external forces is reduced, and the material is very prone to chain bonding under high temperature and high humidity environments. The segments move, resulting in a decrease in viscosity; from the results of Comparative Example 3 and Example 2, it can be seen that the unmodified graphite and graphene in Comparative Example 3 are easy to agglomerate and difficult to be evenly dispersed in the matrix. There is a lack of surface modification, and the interface bonding force between the filler and the polyimide matrix is ​​weak. The agglomeration of the filler leads to an increase in internal defects of the material and a loose network structure. Under conditions of high temperature and high humidity, the polymer chain segments are easier to move, and the viscosity is significantly reduced; from the results of Comparative Example 4 and Example 2, it can be seen that in Comparative Example 4, ethyl acetate is a protic solvent, and its solubility is not as good as that of N,N-dimethylformamide. It cannot effectively dissolve the polyimide precursor and disperse the filler. The filler is difficult to be evenly dispersed in the solvent, resulting in serious agglomeration. The material is more easily degraded under conditions of high temperature and high humidity, and the viscosity is significantly reduced.

[0034] Peel strength test: Using the polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4, the polyimide film was cut into strips with a width of 25 ± 0.5 mm and bonded to a glass slide of the same width. The average peel force at a speed of 100 mm / min was tested using a universal material testing machine. The peel strength was calculated based on the peel force (no less than 5 samples for each pattern). Peel strength (N / cm) = peel force / bonding width. The results are shown in the figure. Figure 3 shown.

[0035] Depend on Figure 3It can be seen from the results that the polyimide mixed glue prepared by the present invention has excellent peel strength. From the results of Comparative Example 1 and Example 2, it can be seen that in Comparative Example 1, there is a lack of modified graphite as an additional reinforcement phase, and the thermal conductivity path and interface bonding in the glue are relatively discontinuous, resulting in a decrease in the overall strength of the material; from the results of Comparative Example 2 and Example 2, it can be seen that in Comparative Example 2, there is a lack of graphene modified by a bifunctional coupling agent, resulting in poor flexibility and toughening effects of the material, and relatively few interface bonding sites. Under stress, the lack of reinforcement of modified graphene reduces the stability of the interface layer, and it is easy to detach due to local stress concentration, and the peel strength is low. The degree is poor; from the results of Comparative Example 3 and Example 2, it can be seen that the unmodified graphite and graphene in Comparative Example 3 have poor dispersibility in the matrix, are easy to agglomerate or form interface defects, resulting in insufficient interface bonding force, loose overall structure, unable to effectively conduct and disperse stress, and significantly reduced peel strength; from the results of Comparative Example 4 and Example 2, it can be seen that the polarity of ethyl acetate in Comparative Example 4 is relatively low, which is not conducive to the dissolution and dispersion of the polyimide precursor, which may lead to poor uniformity and interface bonding force of modified graphite and graphene, and the composite material cannot form a uniform interface structure, resulting in stratification and uneven adhesion effect, and extremely poor peel strength.

[0036] Tensile strength test: The polyimide mixed glue prepared in Example 2 of the present invention and Comparative Examples 1 to 4 was evenly poured into a 0.5 mm × 150 mm × 10 mm polytetrafluoroethylene strip mold, and cured into a solid strip of adhesive film under the same curing process. Three strips of each sample were tested for tensile strength. The results are as follows: Figure 4 shown.

[0037] Depend on Figure 4 The results show that the polyimide mixed glue prepared by the present invention has excellent tensile strength. The results of Comparative Example 1 and Example 2 show that the modified graphene in Comparative Example 1 is multi-bonded by a bifunctional coupling agent to form a certain "stress buffer zone", but the single modified graphene is poor in dispersibility and filling uniformity, and the tensile strength is reduced; the results of Comparative Example 2 and Example 2 show that the toughening and interface bonding network of graphene are lacking in Comparative Example 2, so that the stress dispersion effect of the material when subjected to force is poor, especially in the tensile direction, it is easier to break and the tensile strength is poor; the results of Comparative Example 3 and Example 2 show that the dispersion of graphite and graphene in the polyimide matrix in Comparative Example 3 is poor, the interface bonding is weak, the agglomeration phenomenon and the interface defects lead to stress concentration, and the tensile strength is significantly reduced; the results of Comparative Example 4 and Example 2 show that ethyl acetate in Comparative Example 4 as a low-polarity solvent is not conducive to the dispersion of graphite and graphene, resulting in limited solubility and dispersibility of each component in the composite matrix, extremely poor interface bonding, and significantly reduced tensile strength.

[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polyimide mixed glue containing graphite and graphene, characterized in that: The composition includes the following components by weight: 4 to 6 parts of modified graphite, 1 to 2 parts of modified graphene, 45 to 50 parts of N, N-dimethylformamide, 10 to 12 parts of rigid diamine monomers, 8 to 10 parts of flexible diamine monomers, 6 to 8 parts of diamine monomers containing ester groups in the main chain and 18 to 20 parts of aromatic anhydride monomers.

2. The polyimide mixed glue containing graphite and graphene according to claim 1, characterized in that: The specific preparation steps of the modified graphite are as follows: A1: After washing the graphite with deionized water, dry it to constant weight to obtain dry graphite; add 3-aminopropyltriethoxysilane into anhydrous ethanol, stir and dissolve evenly to obtain a coupling agent solution; A2: adding the dried graphite prepared in step A1 to the coupling agent solution prepared in step A1, after ultrasonic treatment, heating to a certain temperature, continuously stirring, centrifuging, filtering, and vacuum drying to constant weight to obtain modified graphite; In step A2, the ratio of the amount of the dry graphite to the coupling agent solution is 1 g: 30-50 mL.

3. The polyimide mixed glue containing graphite and graphene according to claim 2, characterized in that: The specific preparation steps of the modified graphene are as follows: B1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature, stir and mix to disperse evenly, control the temperature, slowly add potassium permanganate, raise the temperature, stir and react, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge, repeatedly wash with deionized water and 1M HCl solution, dry to constant weight, and obtain graphene oxide; B2: dispersing the graphene oxide prepared in step B1 in dimethyl sulfoxide, and ultrasonically treating the dispersion to obtain a graphene oxide dispersion; slowly dropping 3-aminopropyltriethoxysilane into the graphene oxide dispersion, controlling the temperature and continuously stirring, and after the dropping is completed, heating and continuously stirring, and cooling to room temperature after the reaction is completed to obtain an amination graphene solution; B3: Add succinic anhydride to the amino graphene solution prepared in step B2, stir and heat, and after reaction, cool to room temperature, repeatedly wash with deionized water and ethanol, centrifuge, and dry to constant weight to obtain modified graphene.

4. The polyimide mixed glue containing graphite and graphene according to claim 3, characterized in that: In step B1, the ratio of the amount of the graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-5mL:1g; in step B2, the ratio of the amount of graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 2mg:1-2mL:0.02-0.03mL; in step B3, the mass ratio of the succinic anhydride to the graphene oxide in step B2 is 1:

5.

5. The polyimide mixed glue containing graphite and graphene according to claim 4, characterized in that: The rigid diamine monomer is any one of p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)diaminobiphenyl and 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl.

6. The polyimide mixed glue containing graphite and graphene according to claim 5, characterized in that: The flexible diamine monomer is any one of 4,4'-diaminodiphenyl ether, bis(4-aminophenyl)terephthalate, 1,3'-bis(4'-aminophenoxy)benzene and 2,2'-bis[4-(4-aminophenoxyphenyl)propane].

7. The polyimide mixed glue containing graphite and graphene according to claim 6, characterized in that: The ester group-containing diamine monomer is any one of [4-(4-aminobenzoyl)oxyphenyl]4-aminobenzoate and bis(4-aminophenyl)terephthalate.

8. The polyimide mixed glue containing graphite and graphene according to claim 7, characterized in that: The aromatic anhydride monomer is selected from any one of p-phenylene-diphthalic acid dianhydride, 4,4-oxydiphthalic anhydride, 4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, 4,4'-biphenyltetracarboxylic anhydride and 3,3',4,4'-benzophenonetetracarboxylic anhydride.

9. A polyimide mixed glue containing graphite and graphene according to any one of claims 1 to 8, characterized in that: The specific preparation steps are as follows: S1: After the modified graphite and modified graphene are ground and screened, they are added to N,N-dimethylacetamide, subjected to ultrasonic treatment, stirred, and uniformly dispersed, and then rigid diamine monomer and flexible diamine monomer are added in sequence at room temperature, stirred and dissolved uniformly, and allowed to stand to obtain a precursor mother solution; S2: Under nitrogen protection, the temperature is raised, and the aromatic anhydride monomer is dried and added to the precursor mother solution prepared in step S1 in batches. After the aromatic anhydride is added, the temperature is gradually raised and stirred continuously. After the reaction is completed, the mixture is allowed to stand and cool to room temperature to obtain a mixed solution; S3: adding a diamine monomer containing an ester group in the main chain to the mixed solution prepared in step S2 in three batches, stirring continuously, standing at room temperature, then raising the temperature, stirring continuously, evaporating under reduced pressure, removing the solvent, and cooling to room temperature to obtain a polyimide mixed glue; The specific parameters of the reduced pressure evaporation in step S3 are temperature 40-50° C., pressure 150-300 mbar, rotation speed 100-200 rpm, and time 1-3 h.

Citation Information

Cited By

  • Preparation method of polyimide base film for heat-conducting graphite film

    CN121628156A